Electrodeposition of Polyaniline on Tantalum: Redox Behavior, Morphology and Capacitive Properties - Chrysanthi Gkili; Konstantinos Deligiannakis; Eirini Lappa; Chrysanthi Papoulia; Dimitra Sazou (Molecules, 2023)
Polyaniline (PANI) is among the most widely studied conducting polymers due to its potential technological applications in various fields. Recently, PANI-based hybrid materials have played an important role in the development of energy storage and conversion systems. The aim of the present work is the investigation of the simultaneous electrochemical growth of PANI and Ta2O5 on the Ta substrate and the characterization of the morphology, redox behavior and pseudocapacitive properties of the resulting micro- or nanostructured composite thin films. A well-adherent conductive Ta2O5-PANI composite film was first formed using cyclic voltammetry on Ta that facilitates the on-top electrodeposition of single PANI via an autocatalytic mechanism. The electrochemical characterization of the Ta|Ta2O5-PANI|PANI electrodes reveals unique redox properties of PANI not shown previously upon using PANI electrodeposition on Ta. Scanning electron microscopy shows that the morphology of the electrodeposited films comprises nano- or microspheres that may develop into nano- or microrods when the polymerization proceeds. Preliminary evaluation of the capacitive properties of the Ta|Ta2O5-PANI|PANI electrode shows adequately high specific capacitance values as high as 1130 F g−1 (at 9.2 mA cm−2), depending on the electrochemical parameters, as well as adequate stability (~80% retention after 100 cycles), indicating their potential application as energy storage devices.